PHYTOCHEMICAL ANALYSIS OF ECENG GONDOK (Eichhornia crassipessolms) OF AGRICULTURAL WASTE AS BIOSENSITIZER FOR FERRI PHOTOREDUCTION - Johnly Alfreds Rorong; Sudiarso Sudiarso; Budi Prasetya; Jeany Polii-Mandang; Edi Suryanto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
It has been done analysis for the total phenolic, flavonoid and tannin compounds at eceng gondok leafs (Eichornia crassipessolms). The research was done in several stages: sample preparation, maceration extraction, evaporation. The total phenolic content analysis by Folin Ciocalteu 50%, flavonoid by chloride aluminium 2% in ethanol, and tanin by vanillin 4% solution in methanol, continued by using ultra violet visible (UV-Vis) spectrophotometry methods. The results showed that the total phenolic content of eceng gondok with methanol 60% of 2.72mg galic acid/kg sample is the high total phenolic content and the lowest phenolic total at aquades of 1.07mg galic acid/kg and the flavonoid with methanol 80% solution of 3.29mg kuersetin/kg is the high flavonoid content, and the lowest at the aquades of 1.65mg kuersetin/kg and the high condensed tannin content with methanol 80% of 0.7mg katekin /kg. The Fe2+ content photoreduction process, with methanol 60% solution showed the Fe2+ production increase of 17.67ppm, aquades of 2.94ppm. Extract that does not contain eritosin as sensitizer only produce Fe2+ of 5.6ppm and that is not illuminated only 0.06ppm Keywords: phytochemical, agricultural waste, eceng gondok, biosentizer, ferric photoreduction mitratani